Linguistic Construction of Ethnic Borders - Jungbluth, Konstanze; Zinkhahn Rhobodes, Dagna; Rosenberg, Peter (Peter Lang International Academic Publishers, 2015)
This volume focuses on the linguistic constructs involved in ethnic borders. Ethnic borders have proven themselves to be surprisingly long-lived: in nearly all European countries and beyond, border demarcation, exclusion of foreigners, and minority conflicts are some of the most persistent challenges for nations and societies. Which linguistic factors play a role in the formation of these borders, especially those drawn along ethnic lines? Which linguistic constructs contribute to the negotiation, establishment and maintenance of ethnic groups and identities? Under which conditions can processes of linguistic convergence, hybrids, or transcultural identities be observed?